Public Infrastructure Towards Economic Growth in Bali Province - Fitri, Desika Eka; Wahyunadi, Wahyunadi (PT FORMOSA CENDEKIA GLOBAL, 2024)
If there is adequate and equitable infrastructure, people can access and carry out economic activities. If economic activities run well, economic growth will increase. This study uses a descriptive quantitative and associative approach to determine how public infrastructure contributes to the economic growth of Bali Province. The study covers all regencies and cities in Bali Province and uses secondary data through panel data regression analysis using the Fixed Effects Model (FEM). Hypothesis testing results show that the infrastructure components of roads, electricity, and markets have a significant influence on economic growth. However, the clean water infrastructure component does not have a significant effect. It is expected that the government pays special attention to infrastructure development that can help economic growth in terms of quantity and quality.